Tren Penelitian Bioetika, Genetika, dan Pendidikan dalam Konteks Muslim: Analisis Bibliometrik (2016–Mei 2026) - Ridha Aulia; Muhammad Rizki Fadil; Achmad Luthfi Chakim; Sazkia Nazilla; Dewi Wulandari (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Rapid advancements in genomics, genetics, and biotechnology have generated ethical challenges that require scholarly engagement, including in Muslim contexts. This study maps global publication trends on bioethics, genetics, biotechnology, and education in Muslim contexts from 2016 to May 13, 2026. Data were retrieved from the Scopus database using a predefined search string and screened through a PRISMA-based selection procedure. Of the 343 records initially identified, 130 documents met the inclusion criteria. Bibliometric data were analyzed descriptively and visualized using VOSviewer to examine publication trends, source productivity, keyword co-occurrence, and collaboration networks. The findings show growing scholarly attention to bioethics and health-related issues, particularly since 2022, with bioethics and Islam serving as central thematic nodes. However, education-related terms, especially those connected to Islamic education beyond medical education, are relatively underrepresented in the analyzed dataset compared with health-oriented bioethics themes. This pattern indicates that existing Scopus-indexed literature has more strongly developed clinical, biomedical, and normative-religious discussions than curriculum- or pedagogy-focused studies. As a descriptive bibliometric study, this article does not evaluate curriculum quality or the actual implementation of bioethics education. Instead, it identifies a thematic gap that should be examined further through qualitative, curriculum-focused, and institution-based research in Islamic educational settings.